Judicial Influence on Academic Decision-Making: A Study of Tenure Denial Litigation Cases in which Higher Education Institutions Did Not Wholly Prevail - Flood, Julee Tate (2012)
This study examined judicial influence on academic decision-making by identifying factors in the tenure process that have induced courts to rule against higher education institutions in litigation stemming from tenure denials. Many interdisciplinary legal and educational studies have been conducted pertaining to tenure related litigation using qualitative, quantitative, and legal research methodologies. Empirical studies have been directed at varied issues, such as the peer review process; specific claims, such as discrimination; types of institutions; or time periods. Much of this scholarship has noted the importance of judicial deference to decisions made in academia. Unique to this study was the application of dual conceptual frameworks of shared governance and judicial deference as to decisions made in the academic tenure denial process. The study was also unique in that it was limited to tenure litigation cases in which institutions did not wholly prevail. Included in the study were published judicial opinions from the period of 1972 to 2011 from the U.S. Supreme Court, U.S. Courts of Appeal, and states’ highest appellate courts. The study sought to determine first, the policies and procedures employed in public and private colleges and universities that have contributed to federal and state appellate courts’ unfavorable rulings against institutions in tenure denial litigation; second, the remedies granted to faculty plaintiffs who prevail in tenure denial litigation; and finally, the steps that colleges and universities can take to minimize and mitigate tenure denial litigation. Complementary legal and qualitative research methods yielded evidence that courts were highly deferential to academic decision-making and that courts ruled against institutions’ tenure decisions when the decisions were contrary to law. Courts granted legal and equitable remedies when institutions infringed upon a professor’s rights, discriminated against a professor, or breached a contract with a professor. Based on the analysis of case law, this study proposed steps that institutions could take to avoid or mitigate tenure denial litigation. By gaining a better understanding of potential flaws in the tenure process and why courts have substituted judicial decisions for those of institutional decisions, this study contributes to our understanding as to how to decrease the influence of the courts on decisions made in academia